2006
DOI: 10.1007/s11468-006-9020-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nanoparticle Size for Plasmonic Enhancement of Fluorescence

Abstract: This paper reports on the enhancement of fluorescence that can result from the proximity of fluorophores to metallic nanoparticles (NPs). This plasmonic enhancement, which is a result of the localized surface plasmon resonance at the metal surface, can be exploited to improve the signal obtained from optical biochips and thereby lower the limits of detection. There are two distinct enhancement effects: an increase in the excitation of the fluorophore and an increase in its quantum efficiency. This study focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 17 publications
1
87
0
11
Order By: Relevance
“…Additionally the excitation rate intensity was directly proportional to the square of local field amplitude. 11,30 Upon excitation of surface plasmon by light, charges would be concentrated at the metal-dielectric interface resulting in a strong amplification of local electric field (known as "lighting rod effect") which greatly enhanced the excitation rate of fluorescein moities in the vicinity of silver nanoparticles. 33 Enhanced local electro- magnetic field in close proximity to the metal nanoparticles accounted for the increased absorption cross section of the fluorophores which further facilitated enhanced fluorescence emission intensity.…”
Section: 29mentioning
confidence: 99%
“…Additionally the excitation rate intensity was directly proportional to the square of local field amplitude. 11,30 Upon excitation of surface plasmon by light, charges would be concentrated at the metal-dielectric interface resulting in a strong amplification of local electric field (known as "lighting rod effect") which greatly enhanced the excitation rate of fluorescein moities in the vicinity of silver nanoparticles. 33 Enhanced local electro- magnetic field in close proximity to the metal nanoparticles accounted for the increased absorption cross section of the fluorophores which further facilitated enhanced fluorescence emission intensity.…”
Section: 29mentioning
confidence: 99%
“…A critical need is to tune the distance between fluorophores and AuNPs in order to overcome nanometal-induced quenching for preparing plasmonic fluorescent nanocomposites. 2 Cyanine dyes are known to form fluorescent J-aggregates upon a wide variety of scaffold materials. 3 During a literature review of chromophore assemblies on metal nanostructures, we found several papers reporting no fluorescent J-aggregates being formed or the fluorescence from such aggregates was quenched or photobleached.…”
Section: Introductionmentioning
confidence: 99%
“…Dye-doped silica nanoparticles [13][14][15] (NP) stand out as excellent candidates as it is possible to dope silica NPs with a large number of fluorophores, increasing the total fluorescence of the label significantly [16,17]. Moreover, the fluorophore is protected inside a silica matrix, thereby increasing photostability [18,19] and quantum efficiency [20,21]. Silica NPs are also relatively non-toxic, chemically inert, and can be prepared in a range of sizes [22].…”
mentioning
confidence: 99%